Biological characteristics of Streptomyces albospinus CT205 and its biocontrol potential against cucumber Fusarium wilt. Issue 7 (2nd July 2016) - Wang, Shimei; Liang, Yin; Shen, Ting; Yang, Hua; Shen, Biao
ABSTRACT: In a dual-culture assay, Streptomyces albospinus CT205 inhibited the growth of Fusarium oxysporum in vitro, the casual agent of widespread Fusarium wilt, probably due to the production of chitinase, β-glucanase, and a heat-resistant antagonistic substance. Pot and field experiments were performed to investigate the effects of S. albospinus CT205 alone or combined with organic fertiliser (BOF-CT205) on control of Fusarium wilt. Pot experiments showed that BOF-CT205 treatments obtained the lowest disease index (23.2), compared with organic fertiliser (OF, 55.3), strain CT205 (66.2), and control (72.5) treatments. In the field experiment, BOF-CT205 treatment yielded significantly lower disease incidences than the control, with reductions of ca. 55%. Cucumber yields in the same treatments were significantly higher than in the control, with increases of approximately 30% in the OF treatment. The cucumber yield was maximised in the BOF-CT205 in field experiments, reaching 8.3 × 104 kg ha −1 . The application of BOF-CT205 reduced the presence of the pathogen in the cucumber rhizosphere. In conclusion, S. albospinus CT205 was demonstrated to be a promising biocontrol agent for cucumber wilt, and the most effective treatment was the application of BOF-CT205.